Noise detector / Syahrul Aizam Ibrahim and Mohd Sani Noor Zailani - Ibrahim, Syahrul Aizam; Noor Zailani, Mohd Sani (2001)
Today because of electronics,we have capabilities that could not even be dreamed about just a few years ago.In the field of communications many of hearing device are being created for people goods. The project name as noise detector as it can amplify small signal of noise to a bigger signal.This concept are used in a hearing devices to help a they who are not capable in hearing .It also can be modify into a very sensitive device that could be used to spy on someone conversation ( around 20m ). Our noise detector used 9v supply ( can use both battery or electric supply-using FW bridge and transformer to convert 250v to 9v. You’ll be served for more details in our coming page.